Intra-and Intergeneric Similarities of Ribosomal Ribonucleic Acid Cistrons of Free-Living, Nitrogen-Fixing Bacteria - De Smedt, J.; Bauwens, M.; Tytgat, R.; De Ley, J. (International Journal of Systematic and Evolutionary Microbiology, 1980)
14C-labeled ribosomal ribonucleic acid (rRNA) was prepared from Azotobacter chroococcum NCIB 8002, Azotobacter paspali 8A, Azomonas agilis NCIB 8636, Azomonas insignis WR 30, Beijerinckia indica NCIB 8712, and Azospirillum brasilense ATCC 29145. These rRNA’s were hybridized under stringent conditions with filter-fixed deoxyribonucleic acid from a great variety of gram-negative bacteria. Each hybrid was described by: (i) the temperature at which 50% of the hybrid was denatured, and (ii) the percent rRNA binding (amount in micrograms of rRNA duplexed to 100 µg of deoxyribonucleic acid). These data were used to construct rRNA similarity maps. The following conclusions could be drawn concerning rRNA cistron similarities. (i) Bacterial genera with free-living, aerobic, nitrogen-fixing members are very diverse and belong to different rRNA superfamilies. The present family Azotobacteriaceae is not a biological unit, and its status as a family is highly questionable. (ii) Azotobacter chroococcum, Azotobacter vinelandii, Azotobacter beijerinckii, Azotobacter paspali, Azotobacter miscellum, Azotobacter armeniae, and Azotobacter nigricans belong in the genus Azotobacter. Any synonymy of these names remains to be determined. Azomonas agilis, Azomonas insignis, and Azomonas macrocytogenes constitute independent branches, which are about equidistant from Azotobacter and section I of Pseudomonas as presented in Bergey's Manual of Determinative Bacteriology, 8th ed. Xanthomonas, Alteromonas vaga, and Alteromonas communis are located in the same rRNA superfamily. (iii) The genus Beijerinckia appears to be rather heterogeneous. Its closest relatives appear to be Xanthobacter autotrophics, “Mycobacterium” flavum, “Pseudomonas” azotocolligans, “Pseudomonas” diminuta, the authentic rhodopseudomonads, and some other organisms. These organisms belong in the same rRNA superfamily as Azospirillum, Agrobacterium, Rhizobium, Acetobacter, Gluconobacter, and Zymomonas. (iv) Derxia belongs in still another rRNA superfamily, together with Chromobacterium, Janthinobacterium, the Pseudomonas acidovorans and Pseudomonas solanacearum groups, Alcaligenes, and a few other taxa. (v) The following organisms were generically misnamed: “Azomonas insignis” ATCC 12523, “Mycobacterium” flavum 301, “Pseudomonas” azotocolligans ATCC 12417, “Pseudomonas” diminuta CCEB 513, and “Rhodopseudomonas” gelatinosa (all strains examined).